Classification of Five Forest and Associated Typifying Pedons of Mahanadi Catchment (Distt. Raigarh, M.P. India) into Sub-group Level - Biswas, R. R. (Indian Forester, 1986)
During detailed soil survey in lower kelo watershed in Mahanadi catchment area, five typifying pedons from extensive ones have been selected for modern classification and the soils of liripani series have been grouped into lithic Ustorthents, Kutels series into Typic Ustochrepts. Nawangaon series into Oxic Paleustaifs., Balinga series as aeric Vertic Ochraqualfs and the soils of Dhoram series into Aeric Ochraquslfs in sub-group level.